IDENTIFICATION OF SUITABLE FOXTAIL MILLET VARIETY FOR RAINFED ALFISOLS OF SCARCE RAINFALL ZONE - C. RADHA KUMARI, P. SHANTHI, M. NIVEDITHA, K.V.S. SUDHEER, Y. PAVAN KUMAR REDDY and B. SAHADEVA REDDY (The Journal of Research ANGRAU, 2017)
A field experiment was conducted to study the suitability of foxtail millet varieties for alfisols of scarce rainfall zone under rainfed conditions for two consecutive years during kharif, 2014-15 and 2015-16 at Agricultural Research Station, Ananthapuramu of Andhra Pradesh. The treatments consisted of six varieties viz., Narasimharaya, Krishnadevaraya, Srilakshmi, SiA 3085, Prasad and Suryanandi. The results revealed that the varieties SiA 3085 followed by Narasimharaya and Srilakshmi produced significantly higher grain yield as compared to the other tested varieties. Narasimharaya and Krishnadevaraya can be recommended for dual purpose both for grain and straw followed by Srilakshmi variety. The variety SiA 3085 can be recommended for grain production on commercial basis as its potential for production of straw is low